WW2 Memorials and Remembrance: German Military Cemetery in Cassino - Arturo Gallozzi; Michela Cigola; Marcello Zordan; Laura Lucarelli (Histories of Postwar Architecture)
"... May the teaching imparted by the fallen soldiers be a guide to life and peace for the present and future of humanity ...", Walter Trepte, president of the Volksbund Deutsche Kriegsgräberfürsorge, in his speech at the memorial ceremony, for the '' inauguration of the Germanic Military Cemetery of Cassino-Caira, May 4, 1965. The WW2 produced more than 250 thousand victims in central and southern Italy, and particuralry in Cassino territory, very close to the German defensive Gustav line. Aim of this article is the documentation and valorization of these special architectural heritage that are silent witnesses to what the war has destroyed but mostly what peace has been able to rebuild. Today in Cassino area there are five military cemeteries in which rest soldiers of thirteen different nationalities who participated in Montecassino battle: Polish cemetery; Commonwealth cemetery; German cemetery; French cemetery and Italian cemetery. All the memorials were designed by some of the best architects and sculptors of the time and have monumental characteristics. We focus on German military cemetery in Caira (Cassino) designed by German architects Robert Tischler and Gerd Offenberg, both chief architect of the German War Graves Commission “Volksbund Deutsche Kriegsgräberfürsorge” - VDK[1]. [1] All images marked with “VDK Archive” are freely available by the “Volksbund Deutsche Kriegsgräberfürsorge”, all other images and photographs are by authors.